The challenge of rapid diagnosis in oncology: Diagnostic accuracy and cost analysis of a large-scale one-stop breast clinic. (October 2016) - Delaloge, Suzette; Bonastre, Julia; Borget, Isabelle; Garbay, Jean-Rémi; Fontenay, Rachel; Boinon, Diane; Saghatchian, Mahasti; Mathieu, Marie-Christine; Mazouni, Chafika; Rivera, Sofia; Uzan, Catherine; André, Fabrice; et al.
Abstract: Purpose: Rapid diagnosis is a key issue in modern oncology, for which one-stop breast clinics are a model. We aimed to assess the diagnosis accuracy and procedure costs of a large-scale one-stop breast clinic. Patients and methods: A total of 10, 602 individuals with suspect breast lesions attended the Gustave Roussy's regional one-stop breast clinic between 2004 and 2012. The multidisciplinary clinic uses multimodal imaging together with ultrasonography-guided fine needle aspiration for masses and ultrasonography-guided and stereotactic biopsies as needed. Diagnostic accuracy was assessed by comparing one-stop diagnosis to the consolidated diagnosis obtained after surgery or biopsy or long-term monitoring. The medical cost per patient of the care pathway was assessed from patient-level data collected prospectively. Results: Sixty-nine percent of the patients had masses, while 31% had micro-calcifications or other non-mass lesions. In 75% of the cases (87% of masses), an exact diagnosis could be given on the same day. In the base-case analysis (i.e. considering only benign and malignant lesions at one-stop and at consolidated diagnoses), the sensitivity of the one-stop clinic was 98.4%, specificity 99.8%, positive and negative predictive values 99.7% and 99.0%. In the sensitivity analysis (reclassification of suspect, atypical and undetermined lesions), diagnostic sensitivity varied from 90.3% to 98.5% and specificity varied from 94.3% to 99.8%. The mean medical cost per patient of one-stop diagnostic procedure was €420. Conclusions: One-stop breast clinic can provide timely and cost-efficient delivery of highly accurate diagnoses and serve as models of care for multiple settings, including rapid screening-linked diagnosis. Highlights: Eight-year accuracy and economic analysis of a large-scale pilot one-stop breast unit. Exact 1-d diagnosis for 75% of attendees. Excellent sensitivity and specificity for benign or malignant lesions. A quick diagnosis is feasible at affordable cost in a large proportion of patients.